Intrinsic decoherence effect on dynamics of a Λ-type qutrit interacting nonlinearly with a coherent field - A.-B.A. Mohamed (Elsevier, 2022)
In this paper, an intrinsic decoherence model is solved analytically for a Λ-type qutrit interacting with a coherent field through intensity-dependent coupling. The effects of the qutrit-cavity interaction, the intrinsic decoherence and the initial coherent field intensity are examined on some quantum phenomena as: atom population inversion, mixedness, entanglement as well as total correlation. It is found that the increase of the physical parameters, the regular oscillatory behavior of the qutrit-population collapses and revivals are changed remarkably. The interaction between the three-level atom and the coherent cavity field generates a strong mixture, negativity entanglement and total correlation (classical + quantum). The growth, the regularity and the stability of these quantum effects depend on the decoherence and the initial coherent cavity intensity.